2020
DOI: 10.1590/0034-7167-2019-0413
|View full text |Cite
|
Sign up to set email alerts
|

Braden Scale in pressure ulcer risk assessment

Abstract: Objective: To analyze the applicability of the Braden Scale to individuals admitted to an Intensive Care Unit (ICU) with the nursing diagnosis Impaired Physical Mobility, in its prediction potential to develop pressure ulcer (PU). Methods: A cross-sectional, quantitative study that evaluated all patients hospitalized in an ICU between November 2016 and February 2017, with the Braden Scale. Results: The prevalence of PU was 35.8% (24/67), in male individuals 58.3% (14/24), diagnosed with ischemic CVA 51.9% (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 11 publications
2
28
1
17
Order By: Relevance
“…The second most frequently reported diagnoses combination was altered physical mobility and impaired skin integrity. This finding supports previous studies that reported immobility as a risk factor for pressure injury [ 23 , 24 ] and included it in the pressure injury risk assessment scales, such as the Braden scale [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…The second most frequently reported diagnoses combination was altered physical mobility and impaired skin integrity. This finding supports previous studies that reported immobility as a risk factor for pressure injury [ 23 , 24 ] and included it in the pressure injury risk assessment scales, such as the Braden scale [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Critical care resource utilization was captured, including nutrition support (≥75% of nutritional goal, estimated by formula), respiratory therapy including prone positioning, continuous RRT (CRRT), wound/ostomy/continence nursing (WOCN) evaluation, operative management of SF, rehabilitation therapy, palliative care consultation, and limitation of goals of care. Richmond Agitation Sedation Scale (RASS) 26 and Braden scores 27 were calculated at least daily. Use of sedative medications, neuromuscular blockade, and vasopressors was analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…PU risk was assessed by the nurse in charge of the ward and the nurse in the operating room 1 d before the operation and 1 w after the operation. The Braden PU risk assessment scale [ 13 ] is used for evaluation, which includes sensation, activity, humidity, movement, friction, and nutrition, with a total score of 23: extremely high risk: ≤9 points, high risk: 10-12 points, medium risk: 13-14 points, and low risk: 15-18 points; the lower the score, the higher the risk of PU.…”
Section: Methodsmentioning
confidence: 99%